(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Anemia is a pathological disorder of the structure of blood cells, in which the concentration of hemoglobin is reduced. At the same time, the number of red blood cells decreases. Anemia is characterized as a secondary disease and is a symptom of other ailments. Let us examine in detail what anemia is, what are the causes and symptoms of its occurrence, and how anemia can be cured.